Impact of dietary practices and physical activity on obesity and overweight in Omani adults and effectiveness of lifestyle interventions using smart phone applications - Al Zuhaibi, Khalid (2018)
Overweight and obesity in Oman have increased dramatically in recent years and are associated with increases in cardiovascular disease and diabetes. This project explored the food choices, dietary intake and physical activity of Omani adults. The effectiveness of smartphone apps on physical activity behaviours in Omani adults was also investigated. In study 1, a survey was conducted on 500 healthy adults living in Oman during the period from December 2013 to April 2014. Eligible participants completed questionnaires, specifically designed for this study and administrated by trained health educators in all governorates in Oman. 55% of the population studied were either overweight or obese (particularly those over 30y of age). BMI was significantly (p<0.05) affected by gender and age group but not by residential area (urban vs rural). Dietary analysis indicated a high consumption of ‘fast food’ but total energy intakes failed to explain the high incidence of obesity. However, the questionnaire indicated a high level of physical inactivity within the population. Study 2, implemented in two phases, aimed to investigate the efficacy of three smartphones apps (MapMyFitness, Lose it, and Pacer) on improving physical activity in Omani male and female adults. Phase1 studied male and female Omani citizens living in the UK while phase 2 specifically investigated females living in Oman. Both phases showed significant increases in physical activity amongst the participants though, due to the short period of intervention (4 weeks), this was associated with only modest changes in BMI. The prevalence of overweight and obesity amongst adults highlights the need for intervention strategies, targeting unhealthy lifestyle behaviours, to curb the prevalence of NCDs in Oman. Smartphone apps, represent potential tool to facilitate changes in lifestyle factors associated with the high prevalence obesity in Omani adults. Key words: Obesity, physical activity, energy intake, MapMyFitness, Lose it, Pacer, Oman.